26 Archives of Maryland 256 (1906) - (:unkn) unknown (My University, 1704)
An Act relating to Servants and Slaves: "that every Man Servant shall at such time of expiration of his as aforesaid have allowed and given him..one Ax and one Gunne of twenty shillings price not above four foot by the barrell nor less than three and an half which said Gunn shall by the Master or Mistress in the presence of the ext Justice of the peace be delivered to such ffreeman under the penalty of five hundred pounds of Tobacco on such Master or Mistress omitting so to do and the like penalty on the said ffreeman selling or disposing thereof within the Space of twelve months..."
Keywords: GUARANTEED RIGHT